ANALISIS RELASI SOSIAL ANTARA PENJUAL DAN PEMBELI DI PASAR IKAN FLAMBOYAN PONTIANAK - Pratiwi, Nidya; Bahari, Yohanes; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was entitled Analysis of Social Relations between Sellers and Buyers in Flamboyan Fish Market Pontianak. This study aimed to determine how the form of cooperation in the form of bargaining (bargaining process) and the social relations of sellers and buyers in the process of permanent buyers in Flamboyan Fish Market Pontianak. The research method used was qualitative research with descriptive methods. Data collection techniques used was observation, interviews, and documentation studies. The results of this study indicated that 1) The social relations of sellers and buyers in the form of bargaining cooperation, namely by planning negotiation targets with the buyer (being friendly), the seller's strategy in the negotiation target (buying and selling agreement), negotiation results (buying and selling) 2) Relationships social seller and buyer in the process of permanent customers, the seller provides quality goods, the seller sets the price, the seller conducts promotions, and the seller establishes a social relationship with the buyer.Key words: Social Relations, Sellers Buyers, MarketÂ